Pengembangan E-LKPD Berbantuan Kahoot Untuk Meningkatkan Kemampuan Pemahaman Konsep Matematis Siswa Kelas VIII SMP Negeri 13 Pontianak dalam Materi Statistika - Mya Putri Puspitasari; Syarifah Fadillah; Abdillah (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2026)
This study aimed to develop an Electronic Student Worksheet (E-LKPD) assisted by Kahoot to improve students' mathematical conceptual understanding on statistics material for eighth-grade students of SMP Negeri 13 Pontianak. The research employed a Research and Development (R&D) approach using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects consisted of six validators, including three material experts and three media experts, as well as 24 students of class VIII B. Data collection instruments included expert validation sheets, teacher and student response questionnaires, and tests of mathematical conceptual understanding. The results showed that the developed E-LKPD achieved a validity score of 92.36% from media experts and 90.83% from material experts, both categorized as very valid. The practicality test resulted in an average score of 91.97%, categorized as very practical. The effectiveness test showed a significant improvement in students' mathematical conceptual understanding, indicated by the Wilcoxon Signed-Rank Test with a significance value of 0.000 < 0.05 and an N-Gain score of 0.54 in the moderate category. Therefore, the Kahoot-assisted E-LKPD is valid, practical, and effective for improving students' mathematical conceptual understanding in statistics learning. Keywords: E-LKPD, Kahoot, Mathematical Conceptual Understanding, Statistics, ADDIE